Biomarkers and bioindicators of the environmental condition using a fish species (Pimelodus maculatus Lacepède, 1803) in a tropical reservoir in Southeastern Brazil - Araújo,F. G. (2018)
Abstract The Funil Reservoir receives a large amount of xenobiotics from the Paraíba do Sul River (PSR) from large number of industries and municipalities in the watershed. This study aimed to assess environmental quality along the longitudinal profile of the Paraíba do Sul River–Funil Reservoir system, by using biomarkers and bioindicators in a selected fish species. The raised hypothesis is that Funil Reservoir acts as a filter for the xenobiotics of the PSR waters, improving river water quality downstream the dam. Two biomarkers, the ethoxyresorufin–O–deethylase activity (EROD), measured as fluorimetricly in S9 hepatic fraction, and the micronuclei frequency (MN), observed in erythrocytes of the cytoplasm, and three bioindicators, the hepatosomatic index (HSI), gonadosomatic index (GSI) and condition factor (CF) were used in Pimelodus maculatus, a fish species widely distributed in the system. Four zones were searched through a longitudinal gradient: 1, river upstream from the reservoir; 2, upper reservoir; 3, lower reservoir; 4, river downstream of the reservoir. EROD activity and HSI and GSI had significant differences among the zones (P<0.05). The upper reservoir had the lowest EROD activity and HSI, whereas the river downstream of the reservoir had the highest EROD and lowest GSI. The river upstream from the reservoir showed the highest HSI and GSI. It is suggested that the lowest environmental condition occur at the river downstream of the reservoir, where it seems to occur more influence of xenobiotics, which could be associated with hydroelectric plant operation. The hypothesis that Funil reservoir acts as a filter decanting pollution from the Paraíba do Sul River waters was rejected. These results are novel information on this subject for a native fish species and could be useful for future comparisons with other environments.